ANALISIS PENGARUH KOMPETENSI, INDEPENDENSI, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS HASIL PEMERIKSAAN PAJAK - Kristiyanto, Agus (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2014)
This research aims to examine and analyze the influence of competence, independence, andinformation technology usage on tax audit quality. Population in this research is entire tax auditors exist inMedium Tax Offices located in Jakarta. The sampling method in this research use proportional simple randomsampling. Data used in the research is primary data obtained through questionnaires from 142 respondents. Themethod of data analysis used is multiple regression analysis with SPSS 17.0. The results showed that each independent variable competence and information technology usagehave significant influence toward tax audit quality, while independence did not have significant influence. Thisresearch results also showed that all independent variables competence, independence, and informationtechnology usage have symultant significantly influence on tax audit quality. Value of the coefficient ofdetermination indicates that together competence, independence, and information technology usage contributeto the dependent variable (tax audit quality) of 63,4%, while the remaining 36,6% are influenced by otherfactors outside the model. Implications of these findings for efforts to increase of audit quality are each taxauditor has to increase their competence and information technology usage